Another Generation of Fundamental Considerations in Language Assessment A Festschrift in Honor of Lyle F. Bachman - Ockey, Gary J.; Green, Brent A.; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2020)
This edited book is a collection of papers, written by language assessment professionals to reflect the guidance of Professor Lyle F. Bachman, one of the leading second language assessment experts in the field for decades. It has three sub-themes: assessment of evolving language ability constructs, validity and validation of language assessments, and understanding internal structures of language assessments. It provides theoretical guidelines for practical language assessment challenges. Chapters are written by language assessment researchers who graduated from the University of California, Los Angeles, where Professor Bachman trained them including the book editors.
1. Introduction -- 2. A Step toward the Assessment of English as a Lingua Franca -- 3. Revisiting the Role of Content in Language Assessment Constructs -- 4. What does Language Testing have to Offer to Multi-modal Listening? -- 5. Learner Perceptions of Construct-centered Feedback on Oral Proficiency -- 6. A Case for an Ethics-based Approach to Evaluate Language Assessments.
Keywords: Language and education; Assessment; Language and languages$1 (BStudy and teaching.s; Language Education; Assessment, Testing and Evaluation; Language Teaching